2011
DOI: 10.1007/s13562-010-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional complementation of rice blast resistance gene Pi-k h (Pi54) conferring resistance to diverse strains of Magnaporthe oryzae

Abstract: Blast disease of rice, caused by Magnaporthe oryzae is an explosive disease that can spread rapidly in conducive conditions. R-gene mediated resistance offers an environmentally sustainable solution for management of this important disease of rice. We have earlier identified a unique R-gene of rice, on chromosome 11 of Oryza sativa ssp. indica cultivar Tetep. In this study we report functional validation of the Pi-k h (Pi54) gene using complementation assay. The blast resistance candidate gene Pi-k h (Pi54) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 36 publications
2
70
0
Order By: Relevance
“…Strategies aimed at breeding for durable blast resistance rice cultivars have focused on the possibility of stacking of multiple R-genes or transferring broad spectrum disease resistance genes in cultivated varieties ). In the present study, we used allele mining approach to clone a novel orthologue of durable rice blast resistance gene Pi54 (Rai et al 2011). In the present investigation, the expression of Pi54 orthologue was confirmed in the blast-resistant wild species of rice, O. rhizomatis using real-time PCR, postinoculation with the pathogen M. oryzae isolate PLP-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies aimed at breeding for durable blast resistance rice cultivars have focused on the possibility of stacking of multiple R-genes or transferring broad spectrum disease resistance genes in cultivated varieties ). In the present study, we used allele mining approach to clone a novel orthologue of durable rice blast resistance gene Pi54 (Rai et al 2011). In the present investigation, the expression of Pi54 orthologue was confirmed in the blast-resistant wild species of rice, O. rhizomatis using real-time PCR, postinoculation with the pathogen M. oryzae isolate PLP-1.…”
Section: Discussionmentioning
confidence: 99%
“…One of the recent approaches used for cloning new and better forms of disease resistance genes is allele mining for which the nucleotide sequence of the gene should be known. The dominant blast-resistant gene, Pi54 cloned from the indica rice line Tetep, associated with resistance to rice blast disease prevalent in different parts of India, has been mapped, cloned and characterized (Sharma et al 2005a, b;Rai et al 2011;Gupta et al 2012). Thus, allele mining for Pi54 orthologue from wild species of rice, O. rhizomatis can be a potential tool for finding alternate and better forms of the gene that can be used for rice blast management.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we have cloned blast resistance gene Pi54 from rice cultivar 'Tetep'. It shows broad spectrum resistance against several isolates prevalent in India [100]. We are also in the process of cloning of its counterpart avirulence gene, AvrPi54, from M. oryzae isolate RML-29 which is avirulent on Pi54 containing genotypes and the pathogen inducible promoter from rice plant itself which is responsive to a broad range of M. oryzae isolates and carry out early induction of downstream genes (unpublished findings).…”
Section: R-avr Two Component System: Designing Broad Spectrum Blast Rmentioning
confidence: 99%
“…Through complementation test, the Pi54 gene was found to confer resistance to four different isolates of the blast fungus in transgenic lines TP-Pi54-2 and TP-Pi54-15, among others. The gene was found to induce the synthesis of callose (b-1,3 glucan) in response to pathogen challenge, indicating its possible role in the initiation of a defense response cascade in the blast resistant plants [100]. The microarray and enzymatic analyses showed that Pi54 gene activates a cascade of defense response genes in a transgenic line up to T6 generation [35].…”
Section: Molecular Cloning Of Blast Resistance Genesmentioning
confidence: 99%
“…Most are dominant, except for the recessive gene pi21 (Jeung et al, 2007). Thus far, at least 20 resistance (R) genes have been cloned (Bryan et al, 2000;Liu et al, 2010;Okuyama et al, 2011;Rai et al, 2011;Yuan et al, 2011;Zhai et al, 2011;Hua et al, 2012), many of which have been organized into gene clusters, such as Pi2 loci (Pi2/ Piz-t/Pi9) (Deng et al, 2006;Qu et al, 2006;Zhou et al, 2006) and Pik loci (Pik/Pik-m/ Pik-p/Pi1) (Ashikawa et al, 2008;Yuan et al, 2011;Zhai et al, 2011;Hua et al, 2012). Among the 20 cloned R genes, 18 genes encode nucleotide binding sites and leucine-rich repeat proteins, except for Pi-d2, which encodes a B-lectin receptor kinase (Chen et al, 2006), and pi21, which encodes a proline-rich protein that contains a putative heavy metalbinding domain and protein-protein interaction motifs (Fukuoka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%